The discoveries and artistic talents of Édouard Chatton and André Lwoff, famous biologists. - Soyer-Gobillard, Marie-Odile (Cambridge Scholars Publishing, 2020)
This book explores the life, work and careers of two lovers of marine biology and protists, Edouard Chatton (1883-1947) and his exceptional pupil André Lwoff (1902-1994), later a Nobel Prize winner. Offering descriptions of their discoveries and explanations of their artistic talents, it also presents (annotated in numbers for the first time) the beautiful educational course boards made by Chatton for his students and collaborators. This book will appeal to scientists, biologists, parasitologists, researchers, teachers, and students, and is a tribute to these two great scientists.